1996
DOI: 10.1088/0022-3727/29/5/036
|View full text |Cite
|
Sign up to set email alerts
|

Effective conductivity in association with model structure and spatial inhomogeneity of polymer/carbon black composites

Abstract: The relationship between effective conductivity and cell structure of polyethylene/carbon black composites as well as between effective conductivity and spatial distribution of carbon black are discussed. Following Yoshida's model both structures can, in a way, be said to be intermediate between the well known Maxwell-Garnett (MG) and Bruggeman (BR) limiting structures. Using TEM photographs on composites with various carbon blacks we have observed that the larger is Garncarek's inhomogeneity measure H of two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In regularly distributed systems composed of hard spheres (in 3-dimensions) or hard disks (in 2-dimensions) percolation is only observed close to limiting concentrations [11,246,20,22]. Other studies have shown that not only the percolation of one of the phases but the field, charge [288,239,294,48,295] and particle related issues [212,192,296,297,99,298] should also be considered.…”
Section: Percolation Theorymentioning
confidence: 99%
“…In regularly distributed systems composed of hard spheres (in 3-dimensions) or hard disks (in 2-dimensions) percolation is only observed close to limiting concentrations [11,246,20,22]. Other studies have shown that not only the percolation of one of the phases but the field, charge [288,239,294,48,295] and particle related issues [212,192,296,297,99,298] should also be considered.…”
Section: Percolation Theorymentioning
confidence: 99%
“…This model situation has been assumed in Refs. [9][10][11][12]. However, it has been shown [13] that this idealized for blackwhite micrographs method needs a modification in the case of finite-sized objects like pixels.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has already been explored for other types of systems such as polymer/carbon composites. [19] The electrical resistivity was thus predicted as a function of CNT content with different arrangements (relative CNT and electrical current orientation) using diverse established models. These six models, summarized in Table 4, are those valid for conductivity/resistivity modeling, among many others with different applications.…”
Section: Resultsmentioning
confidence: 99%